The Impact Of The QRIS Payment System On Increasing The Income Of MSMEs In The Restaurant Sector In Medan Sunggal - Rizky Pramudita Bukit; Ahmad Fadlan; Uswatun Hasanah (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to analyze the effect of the implementation of the QRIS payment system on increasing the income of MSMEs in the restaurant sector in Medan Sunggal District, Medan City, where MSMEs play a crucial role in the national economy with a contribution of 60.5% of GDP and absorption of 96.9% of the workforce, but face challenges in access to financing, tight competition and limitations of digital technology. A quantitative approach was applied to 20 samples of MSME restaurants from a population of 21 units that have used QRIS for at least 6 months with data collection through closed questionnaires analyzed using Confirmatory Factor Analysis (CFA) with a KMO value of 0.562> 0.5 and Bartlett's test sig. 0.003 and Multiple Linear Regression after fulfilling classical assumption tests such as normality (Kolmogorov-Smirnov sig. 0.200), multicollinearity (VIF <10) and autocorrelation (Runs Test sig. 0.108). The CFA results identified four main factors from ten independent variables, namely the use of e-commerce applications (X1), online presence on social media (X2), QRIS implementation (X3) and integration with delivery platforms (X4) which explained the total variance of 77.673%. The multiple linear regression model produced the equation Y = 6.066 + 0.253X1 + 0.293X2 + 0.324X3 + 0.249X4, where the use of e-commerce applications (X1) had a positive and significant effect partially (t = 1.892 > t-table 1.753, sig = 0.03 < 0.05). Then the online presence on social media (X2) had a positive and significant effect partially (t = 1.845 > t- table 1.753, sig = 0.01 < 0.05). Then the implementation of QRIS (X3) has a positive and significant effect partially (t = 2.617 > t-table 1.753, sig = 0.01 < 0.05). Then integration with the delivery platform (X4) has a positive and significant effect partially (t = 1.871 > t-table 1.753, sig = 0.02 < 0.05). Meanwhile, the simultaneous test shows F = 4.273 (sig = 0.02) with R² = 0.848 which explains 84.8% of the variation in income. The rest is influenced by external factors in the region. QRIS is proven to be a major catalyst through transaction efficiency without MDR fees for nominal ≤Rp500,000, reduced cash risk and increased customer turnover in busy culinary areas such as Medan Sunggal which has the 20 highest MSME restaurants in Medan.